Sex differences tn perceptions of romantic acts in Portuguese adolescents - Félix Neto (2000)
The study was done to examine sex differences in the importance attributed to romantic acts by adolescents. On a 15-item Romantic Acts questionnaire of Neto participants rated the importance of each act. Four factors of Offerings, Physical Intimacy, Altruistic Behavior, and Sexual Behavior were found. The 108 girls judged physical intimacy as more important than the 79 boys.